Assessment of adverse events and near misses during voluntary community-driven sports activities by community residents: a cross-sectional study - Akihiro Hirata; Yuko Oguma; Takeshi Hashimoto (Japanese Society of Physical Fitness and Sports Medicine, 2024)
Although physical activities have many health benefits, adverse events and near misses, such as injuries and falls, can occur during these activities. This study aimed to assess the occurrence of adverse events and near misses during sports activities conducted independently by community residents. A survey questionnaire was sent via the internet to the leaders or directors of sports organizations at six public sports centers or associations. In total, 108 individuals answered the survey, with 60% male and 40% female respondents. Individuals aged 50-69 years accounted for 60% of the total number of respondents. All respondents were asked about their experiences of adverse events and near misses within the past three years: the reports of these incidents were obtained using the recall method. Duplicate adverse events and near misses were identified based on the sports discipline, time of occurrence, and sex and age of person involved to determine if there were duplicate reports. Most of the respondents' activities as staff were performed once a month, with each activity lasting 1-2 h. Forty-five adverse events were reported, including 26 injuries, 13 falls, and 6 others (such as heat stroke, vertigo, and presyncope). Twenty-four near misses were reported, including 12 near collisions with people or objects, five near falls, and seven other incidents. We found that approximately 30% of the respondents experienced adverse events, suggesting the need for documentation of adverse events, implementation of safety measures, and proper safety education for operating staff.